2019
DOI: 10.1002/biof.1510
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D deficiency increases the thromboxane/prostacyclin ratio through alterations in the one‐carbon cycle in Wistar rats

Abstract: This study aims to test the hypothesis that vitamin D deficiency can influence long‐chain polyunsaturated fatty acid metabolism through alterations in the one‐carbon cycle. Wistar rats (n = 8 per group) were given either a control (1,000 IU D3/kg diet) or a vitamin D deficient (VDD) (0 IU D3/kg diet) diet from pre‐pregnancy to delivery. On day 20 of gestation, pregnant female rats were delivered by C‐section to collect placenta and blood. VDD group demonstrated high serum parathyroid hormone, low serum phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
3
0
2
Order By: Relevance
“…One genetic target of vitamin D is cystathionine β‐synthase (CBS) which is required for transsulfuration pathway, the essentials for homocysteine disposal. In vitro study revealed that vitamin D deficiency induces elevated cellular homocysteine levels 31 and in vivo study showed that vitamin D deficiency was associated with hyperhomocysteinemia which increased thromboxane B2/prostacyclin ratio and induced endothelial dysfunction in pregnant rats 32 …”
Section: Vitamin Dmentioning
confidence: 99%
“…One genetic target of vitamin D is cystathionine β‐synthase (CBS) which is required for transsulfuration pathway, the essentials for homocysteine disposal. In vitro study revealed that vitamin D deficiency induces elevated cellular homocysteine levels 31 and in vivo study showed that vitamin D deficiency was associated with hyperhomocysteinemia which increased thromboxane B2/prostacyclin ratio and induced endothelial dysfunction in pregnant rats 32 …”
Section: Vitamin Dmentioning
confidence: 99%
“…A human study found that after cardioplegia/reperfusion, the human coronary microvasculature showed significantly decreased TXA 2 -induced vasoconstriction compared to that before procedures, while the protein level and gene expression of thromboxane synthase and thromboxane A 2 receptor did not differ in atrial tissue [33]. Vitamin-D-deficient pregnant female Wistar rats had higher placental mRNA levels and lower protein levels of phospholipase A2 and cyclooxigenase-2 compared to the control group, while serum thromboxane B 2 levels were similar between the groups [34]. Moreover, the VDD group had higher liver and plasma arachidonic acid levels than the control one [35].…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, an animal study demonstrates that maternal deficiency of vitamin D influences FA metabolism and alters FA levels (Nandi et al, 2019a). Nandi et al (2019b) observed that maternal vitamin D deficiency increases the ratio of vasoconstrictor and vasodilator lipid metabolites of PUFA by increasing Hcy and oxidative stress levels.…”
Section: Vitamin B12 Statusmentioning
confidence: 99%